Population size and processing time in a genetic algorithm - Reis, Cecília (2019)
This paper presents several experiments with a genetic algorithm (GA) for designing combinational logic circuits. The study addresses the population size and the processing time for achieving a solution in order to establish a compromise between the two parametrs. Furthermore, it is also investigated the use of different gate sets for designing the circuits namely RISC and CISC like gate sets.